The Characteristic Features Of The Work“Beware The Cat” - U.S.Toirova (Euro Asian Journal Publishing, 2025)
Born in Wales around 1515, William Baldwin's literary career began in earnest in 1547 when he worked with printer Edward Whitchurch, whose writings stro ngly supported the Church of England during King Edward’s reign. Baldwin is most known for his seminal work *A Treatise of Morall Phylosophie i n 1547, which stressed the value of ancient knowledge and selfeducation, and his ”Beware the Cat” in 1552, which is widely regarded as the fi rst English novel and creatively explores themes of religion and humanism thro ugh a debate among humanists regarding the ability of animals to speak. Throu ghout his career, Baldwin was a vocal opponent of Catholicism and interacted with the humanist ideas of his time.
Keywords: Edward Whitchurch; Church of England; William Baldwin